Analisis Penyelesaian Perselisihan Hasil Pemilihan Presiden di Indonesia - Prioni Rahmanda Saputri (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
This research is motivated by the Authority of the Constitutional Court in deciding disputes over the results of the Presidential Election in Indonesia. The Constitutional Court has the authority, including deciding disputes over presidential election results, to protect the constitutional rights of citizens, including the right to vote and be elected. Even though the election went smoothly, there was dissatisfaction which gave rise to disputes, which the Constitutional Court had an important role in resolving. This research aims to provide better insight into the role of the Constitutional Court in maintaining integrity and justice in the democratic process in Indonesia, as well as identifying the challenges and opportunities faced in resolving disputes over the results of the presidential election. The method used in this research is normative law with primary and secondary data sources. This research concludes that the discussion highlights the importance of the Constitutional Court (MK) in maintaining integrity and justice in Indonesian democracy. The Constitutional Court, as the front guard in upholding the rule of law and democratic principles, provides confidence that the presidential election is trustworthy and guaranteed to be fair by an independent institution. However, resolving disputes over the results of the Presidential Election faces obstacles such as political contestation and lack of compliance. Strong commitment, mutual understanding, and increased capacity of dispute resolution institutions and law enforcement are needed to overcome these obstacles.